Laser treatment of high strength low alloy steel and electrochemical response of the surface. Issue 2 (9th March 2015) - Yilbas, B. S.; Toor, Ihsan-ul-Haq; Malik, Jahanzaib; Patel, F.
Abstract : Purpose: – The purpose of the present study is to report the results of the laser treatment of high-strength low-alloy (HSLA) steel surface and corrosion response of the treated surface that was carried out. Metallurgical and morphological changes in the laser-treated layer are also examined. Laser treatment of the alloy surface improves the surface properties; however, development of high thermal stress field in the treated layer can exceed the yielding limit of the alloy lowers, particularly, the corrosion resistance of the resulting surface. Design/methodology/approach: – Pre-prepared workpiece surfaces are laser-treated and electrochemically tested in an electrolytic solution. Corrosion rate of the resulting surface is analyzed and pit sites are examined. Findings: – It is found that the presence of nitride compounds and fine grains acts like as a self-protective layer at the laser-treated surface while lowering the corrosion resistance. Consequently, laser gas-assisted treatment provides a positive effect on the corrosion properties of the treated surface through lowering the corrosion current. The pits are shallow and do not form a regular pattern at the workpiece surface. The secondary pitting is prevented by the protective layer formed at the laser-treated surface. Research limitations/implications: – The study can be extended to include laser treatment including the hard particles, such as carbides, at the surface. However, this extension is left to another study. Practical implications: – Laser treatment can be used for protection of surfaces from wear and corrosive environments. The findings of this study give insight into the improvement of the surface characteristics for this purpose. It serves to industry for the practical solution of the surface protection from corrosive environments. Social implications: – The researchers and scientists working in the area get the benefit from the outcome of this work. Originality/value: – It is an original work and gives insight into the enhancement of the corrosion resistance of HSLA steel after the laser treatment process.